2010
DOI: 10.2113/gssgfbull.181.5.429
|View full text |Cite
|
Sign up to set email alerts
|

Inversion tectonics at the northern margin of the Paris basin (northern France): new evidence from seismic profiles and boreholes interpolation in the Artois area

Abstract: A synthesis of existing borehole data and seismic profiles has been conducted in the Artois area (northern France), along the northern border of the Paris basin, in order to explore the possible control exerted at depth by the Upper Carboniferous Variscan thrust front on the distribution of Late Paleozoic-Mesozoic depositional centers and their subsequent uplift in Tertiary times. Such control was demonstrated recently in the Weald-Boulonnais basin (Eastern Channel area) that forms the western prolongation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 35 publications
2
8
0
Order By: Relevance
“…Hence, their original normal offsets would have been much smaller and, so, overcompensated by the Tertiary tectonic inversion. This is consistent with the observations of Minguely et al (2010) and Underhill & Paterson (1998) in the North Artois shear zone (northeastern France) and the Wessex Basin (Southern England), respectively. Both studies showed several examples of faults that offset the upper and younger sedimentary strata reversely, while the offset in the lower and older strata remains normal.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Hence, their original normal offsets would have been much smaller and, so, overcompensated by the Tertiary tectonic inversion. This is consistent with the observations of Minguely et al (2010) and Underhill & Paterson (1998) in the North Artois shear zone (northeastern France) and the Wessex Basin (Southern England), respectively. Both studies showed several examples of faults that offset the upper and younger sedimentary strata reversely, while the offset in the lower and older strata remains normal.…”
Section: Discussionsupporting
confidence: 92%
“…However, considering the amount of deformation necessary to create such large basins, similar offsets should be observable in Quaternary deposits along the on-shore continuation of these structures, which is not the case (e.g. Minguely et al 2010). A tectonic origin of the fosse is thus very unlikely.…”
Section: T E C T O N I C a N D G E O L O G I C A L S E T T I N G Smentioning
confidence: 95%
See 2 more Smart Citations
“…This margin, alike the adjacent North Sea and Wessex basin, was affected by a major Late Jurassic-Early Cretaceous rifting event (Minguely et al, 2010 and reference therein) coeval with the general propagation of the Atlantic rift zone, north of the Gibraltar-Newfoundland fracture zone. The related pattern of subsidence and uplift induced the preservation of shallow marine Upper Jurassic and continental Lower Cretaceous (Wealdian) deposits in a restricted fault-bounded Boulonnais embayment upon which the presentday exposure is molded ( Fig.…”
Section: Geological Framework and Previous Resultsmentioning
confidence: 97%